Enhancing Thermal Efficiency of Lithium-Ion Batteries Using Phase Change Materials: A CFD-Based Comparative Study - Prasetyo, Singgih Dwi (Journal of Research in Nanoscience and Nanotechnology, 2025)
Thermal management plays a vital role in the performance and safety of lithium-ion battery systems, addressing challenges such as overheating and efficiency loss. This study investigates the thermal performance of four different Phase Change Materials (PCMs)—Paraffin, Soywax, Lauric Acid, and Calcium Chloride Hexahydrate—using transient Computational Fluid Dynamics (CFD) simulations via ANSYS Fluent. Five simulation scenarios with iteration counts ranging from 100 to 500 were employed to evaluate heat distribution, phase transition behavior, and thermal and electrical efficiencies. The results demonstrate that Soywax exhibits superior performance with a thermal efficiency of up to 68% and an electrical efficiency reaching 98%. Paraffin also displays significant thermal buffering, achieving a thermal efficiency of approximately 64%. In contrast, Lauric Acid yields moderate thermal efficiency at around 55%, while Calcium Chloride Hexahydrate performs least effectively with a thermal efficiency of only 45% due to its slower heat response. The simulations confirm the necessity for a minimum of 300–400 iterations to capture accurate thermal behavior and ensure numerical stability. Consequently, the findings highlight Soywax and Paraffin as the most viable PCMs for improving battery safety and efficiency, presenting promising avenues for thermal regulation in electric vehicles and energy storage applications.